X-Men : battle of the Sentinels - Hautzig, Deborah; Edens, Mark Edward; Ruiz, Aristides; Yee, Josie (New York : Random House, 1994)
Jubilee, a mutant teen, learns about her special powers from a group of other mutants called the X-Men who are fighting robot police called the Sentinels.
Keywords: Robots; Heroes; Science fiction